Genetic engineering of maize and rice to enhance tolerance against abiotic and biotic stresses - Tamang, Tej Man (Kansas State University, 2021)
Genetic engineering has allowed biologists to make genetic changes for crop improvement. Being sessile, plants are exposed to the different biotic and abiotic stresses throughout their life stages. Numerous genes have been studied to improve pest resistance and abiotic stress tolerance in plants. Here, we expressed Arabidopsis monothiol glutaredoxin gene in maize and studied the effect of the gene in improving drought and heat tolerance. Similarly, we expressed Pi9 gene in elite cultivar of rice to develop the resistance against blast disease through cisgenic approach. Heat and drought are two of the major abiotic stresses that usually appear simultaneously. Various climate models suggest that these stresses will increase in intensity and frequency. The reproductive phases of the development are very sensitive to both drought and high-temperature stress. Reactive oxygen species (ROS) accumulate in response to the stresses and cause oxidative damage to many biological molecules, including lipids, proteins, and DNA. In our study, we performed ectopic expression of Arabidopsis monothiol glutaredoxin, AtGRXS17, to improve tolerance against drought stress and combined heat and drought (HTD) stress at the reproductive stage of maize. Glutaredoxins (GRXs) are oxidoreductases that maintain redox homeostasis. Ectopic expression of the AtGRXS17 in maize resulted in increased tolerance against drought stress and HTD stress. Under both types of stresses, AtGRXS17-expressing maize lines showed higher yields than WT plants. Our results also indicated that AtGRXS17-expressing pollen grains showed better pollen germination than WT under desiccating environment. Despite the huge potential of genetic engineering in improving crops, concerns have been raised about the presence of foreign genes in plants and their unpredictable consequences. Because of this, commercialization of transgenic crops is highly regulated. Removing selection marker and unnecessary transgene can potentially address the biosafety concerns of regulatory bodies. In our research, we demonstrated successful incorporation of a rice blast resistance gene Pi9 into an elite US rice cultivar via cisgenic method. We used a co-transformation strategy to eliminate the marker gene (hygromycin B phosphotransferase) from the cisgenic rice. We also found that the success rate of co-transformation was very low. Nevertheless, the co-transformation approach provides an effective way to develop marker-free cisgenic plants.
Keywords: Drought; AtGRXS17; Rice blast disease; Combined heat and drought; Cisgenesis; Pi9